Second Language Action Words Learning in Chinese EFL Learners Through Fast-Mapping and Explicit Encoding - Yamin Qu (Journal of Linguistics and Communication Studies, 2024)
Research on fast-mapping (FM) and explicit encoding (EE) has focused exclusively on the learning of concrete nouns, and few studies have explored verb learning through FM and EE in speakers’ mother language. The present study aims to investigate the role of fast-mapping and explicit encoding in Chinese EFL learners’ second language action word learning. Forty participants were enrolled and randomly assigned to the FM and the EE group in the experiment, with a 2 (learning procedure) * 2 (test delay) two-way factorial design adopted. After the learning session, participants in both groups completed a series of tests in 10 minutes and again on the next day. The results demonstrate stronger declarative memory of the novel action words through explicit encoding, whereas fast mapping is conducive to learners’ lexical and semantic integration.